High Systemic Immune Inflammation Index Is Associated With Low Skeletal Muscle Quantity in Resectable Pancreatic Ductal Adenocarcinoma - Aziz, Mohammad Hosein; van Dongen, Jelle C.; Saida, Lawlaw; Suker, Mustafa; van Vugt, Jeroen L. A.; van Putten, Yordi; Sideras, Kostandinos; Groen, Jesse V.; Mieog, J. Sven D.; Lucassen, Claudia J.; Droop, Anneke; Mauff, Katya; et al. (Frontiers in Oncology, 2022)
Background and aims: Failing immune surveillance in pancreatic ductal adenocarcinoma (PDAC) is related to poor prognosis. PDAC is also characterized by its substantial alterations to patients’ body composition. Therefore, we investigated associations between the host systemic immune inflammation response and body composition in patients with resected PDAC. Methods: Patients who underwent a pancreatectomy for PDAC between 2004 and 2016 in two tertiary referral centers were included. Skeletal muscle mass quantity and muscle attenuation, as well as subcutaneous and visceral adipose tissue at the time of diagnosis, were determined by CT imaging measured transversely at the third lumbar vertebra level. Baseline clinicopathological characteristics, laboratory values including the systemic immune inflammation index (SIII), postoperative, and survival outcomes were collected. Results: A total of 415 patients were included, and low skeletal muscle mass quantity was found in 273 (65.7%) patients. Of the body composition indices, only low skeletal muscle mass quantity was independently associated with a high (>900) SIII (OR 7.37, 95% CI 2.31-23.5, p=0.001). The SIII was independently associated with disease-free survival (HR 1.86, 95% CI 1.12-3.04), and cancer-specific survival (HR 2.21, 95% CI 1.33-3.67). None of the body composition indices were associated with survival outcomes. Conclusion: This study showed a strong association between preoperative low skeletal muscle mass quantity and elevated host systemic immune inflammation in patients with resected PDAC. Understanding how systemic inflammation may contribute to changes in body composition or whether reversing these changes may affect the host systemic immune inflammation response could expose new therapeutic possibilities for improving patients’ survival outcomes.